Ramón Garcia de Haro, Cristo, fundamento, de la moral, Ediciones Internacionales Universitarias EUNSA, S. A., Barcelona, 1990, 190 pp - Derisi, Octavio Nicolás (1991)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina